The case of the feathered mask - Webb, Holly (Webb, Holly. Mysteries of Maisie Hitchins, 2016)
Junior sleuth Maisie Hitchins, who lives in her grandmother's boarding house in Victorian London, investigates the theft of a rare and valuable tribal mask from the Amazonian rainforest.